Psychosocial and behavioural aspects of early incident response: outcomes from an international workshop - Holly Carter; Louis Gauntlett; G. James Rubin; David Russell; Melissa Genereux; Louise Lemyre; Peter Blain; Mark Byers; Richard Amlôt (Taylor & Francis Group, 2018)
The likelihood of major incidents and disasters has increased in recent years, due to climate change, urbanisation, and acts of terrorism. Effective management of such incidents is crucial to ensure that members of the public are able and willing to take appropriate protective actions. The workshop described in this paper brought together researchers, practitioners and policy makers with expertise in emergency planning, preparedness and response to generate recommendations for major incident management. Workshop participants agreed that understanding the psychosocial aspects of major incidents is crucial to effective incident response, and a number of key themes were raised during workshop discussions. Based on these themes, four key recommendations can be made for informing planning and preparedness for major incidents.